2021
DOI: 10.1001/jamaneurol.2021.2043
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes Over the First Year After Moderate to Severe Traumatic Brain Injury in the Prospective, Longitudinal TRACK-TBI Study

Abstract: IMPORTANCEModerate to severe traumatic brain injury (msTBI) is a major cause of death and disability in the US and worldwide. Few studies have enabled prospective, longitudinal outcome data collection from the acute to chronic phases of recovery after msTBI. OBJECTIVE To prospectively assess outcomes in major areas of life function at 2 weeks and 3, 6, and 12 months after msTBI. DESIGN, SETTING, AND PARTICIPANTS This cohort study, as part of the Transforming Research and Clinical Knowledge in TBI (TRACK-TBI) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
135
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 174 publications
(142 citation statements)
references
References 45 publications
4
135
1
2
Order By: Relevance
“…In contrast to the GOSE, the distribution of DRS scores skewed towards the milder end of the scale, suggesting a greater potential for determining meaningful functional differences between patients with DoC after TBI. However, like the GOSE ≤3 category, we found that common DRS total score groupings reported in prior studies (e.g., Moderate and Moderately-Severe) 2, 8, 37 , also spanned a wide range of FIM total scores. Although there is less precedent for dichotomizing the DRS, we found that a cut-point of at least Severe Disability (DRS ≥12) was a specific, but insensitive marker of FIM-dependency.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…In contrast to the GOSE, the distribution of DRS scores skewed towards the milder end of the scale, suggesting a greater potential for determining meaningful functional differences between patients with DoC after TBI. However, like the GOSE ≤3 category, we found that common DRS total score groupings reported in prior studies (e.g., Moderate and Moderately-Severe) 2, 8, 37 , also spanned a wide range of FIM total scores. Although there is less precedent for dichotomizing the DRS, we found that a cut-point of at least Severe Disability (DRS ≥12) was a specific, but insensitive marker of FIM-dependency.…”
Section: Discussionsupporting
confidence: 62%
“…Our findings highlight the wide range of functional impairment within dichotomized GOSE and DRS categories and demonstrate fundamental differences in the calibration of these outcome scales. Most participants in this study achieved a 1-year GOSE score of 3 (Lower-Severe Disability), just one category above “Vegetative State” and typically considered an ‘unfavorable’ outcome 2, 30-35 . GOSE ≤3 was a highly sensitive but non-specific marker for FIM-dependency.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Their efforts have translated into decreased TBI mortality rates over the past decade in the United States [ 3 ]. Recently it was reported 75% of moderate TBI patients achieve GOSE scores ≥4 at 12 months, and 57% of severe TBI patients achieve GOSE scores ≥5 at six months [ 4 , 5 ]. For clinicians, the Brain Trauma Foundation Guidelines for the Management of Severe TBI is an invaluable resource [ 6 ].…”
Section: Reviewmentioning
confidence: 99%